2017
DOI: 10.7554/elife.21660
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution imaging of a 2.5 kb non-repetitive DNA in situ in the nuclear genome using molecular beacon probes

Abstract: High-resolution visualization of short non-repetitive DNA in situ in the nuclear genome is essential for studying looping interactions and chromatin organization in single cells. Recent advances in fluorescence in situ hybridization (FISH) using Oligopaint probes have enabled super-resolution imaging of genomic domains with a resolution limit of 4.9 kb. To target shorter elements, we developed a simple FISH method that uses molecular beacon (MB) probes to facilitate the probe-target binding, while minimizing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 66 publications
(140 reference statements)
0
26
0
Order By: Relevance
“…Although conventional fluorescence microscopy and flow cytometry demonstrated that the abundance of cell-surface rafts increased during RA-induced differentiation ( Figure 1 ), they failed to reveal the detailed features of these nanoscopic structures. In this regard, we sought to STORM that provides better spatial resolution, e.g lateral resolution of 22 nm in our lab [38]. STORM breaks optical diffraction limit via stochastically activating switchable fluorophores like Alexa Fluor 647 (AF647) at separate times, and the final super-resolution images are reconstructed with the measured positions of these individual fluorophores [7-9].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although conventional fluorescence microscopy and flow cytometry demonstrated that the abundance of cell-surface rafts increased during RA-induced differentiation ( Figure 1 ), they failed to reveal the detailed features of these nanoscopic structures. In this regard, we sought to STORM that provides better spatial resolution, e.g lateral resolution of 22 nm in our lab [38]. STORM breaks optical diffraction limit via stochastically activating switchable fluorophores like Alexa Fluor 647 (AF647) at separate times, and the final super-resolution images are reconstructed with the measured positions of these individual fluorophores [7-9].…”
Section: Resultsmentioning
confidence: 99%
“…A STORM system based on an inverted optical microscope (IX-71, Olympus) with a 100x oil immersion objective lens (UplanSApo, N.A. 1.40, Olympus) was used for the nanoimaging as previously described [38]. A 405 nm laser (CUBE 405–100C; Coherent) was used for photoactivation and a 641 nm laser (CUBE 640–100C; Coherent) was used to excite fluorescence and deactivate Alexa-647 to the dark state.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular beacon resumes fluorescence upon binding to its target. Ni et al () demonstrated the utilization of mbFISH and STORM by imaging a 2.5‐kb nonrepetitive locus. Other techniques, such as fluorescence resonance energy transfer (Auer, Strauss, Schlichthaerle, & Jungmann, ) have also been utilized to eliminate background fluorescence in DNA PAINT.…”
Section: Fluorescence Super‐resolution Imaging and Single‐molecule Trmentioning
confidence: 99%